DATA POTENSI DAN INOVASI PENGEMBANGAN PRODUK GULA MERAH DI DESA KARANG BAYAN UNTUK MENINGKATKAN DAYA SAING GLOBAL - Faris Hidayatullah, Azka; Ahmad Fanani, Labib; Oktapiana, Cici; Alhamah, Isnaini; Ihsoni, Baital; Fatrisiah, Elisa; Aolia, Milna; Wulandari, Radhitia; Wulandari, Nur; Nurrahmah Jannatun, Desi; Faturrahman (Jurnal Wicara, 2025)
Karang Bayan Village has great potential in the agricultural sector, with aren (palm sugar) as its main commodity. However, the unstable price of palm sugar and the limited market reach have resulted in farmers in Karang Bayan Village struggling to earn a sufficient income, especially when palm sugar prices decline. The aim of this activity is to enhance farmers' knowledge regarding attractive packaging processes and digital marketing strategies, ensuring price stability and a broader market reach for palm sugar. The programs implemented in this activity include identifying the potential of palm sugar farmers, training on making and packaging palm sugar in candy form, and socialization on digital marketing. The results of this activity indicate an increase in farmers' understanding of the importance of attractive product packaging and digital marketing strategies. Furthermore, based on the collected data, Karang Bayan Village has significant potential for the further development of the palm sugar commodity.